“Manejo agronómico del cultivo de soya (glycine max (L) merril), en la región San Martín” - Barces Macedo, Jorge Luis (2011)
This engineering report is based on the compilation of results from various literature sources, such as theses, including websites, institutions. Literature and leaflets, whose objectives were to collect and analyze information gathered on the cultivation of soybean ( Glycine max (L) Merrill) and its growing importance in the region of san martín. The results obtained by making the analysis of information gathered highlighted the importance of agricultura! practices such as site preparation, this must be done immediately after harvest and sowing is very important to reduce errors and risks, be more likely to success during the growing cycle and thereby obtain good grain yield of soybean crops in the San Martín region, summarized in two fundamental respects they are: high productivity and profitability. San Martin region has favorable soil and climatic conditions for cultivation, plus the combination of good technology package in crop management, soybean express their true performance potential and will thus be higher income for famers engaged to this activity. In the region of San Martin in the year 200712008 the area sown (Ha) of the soybean crop in 330.00 Ha and production (Tm) soybean crop in 2008 is 298.70 TM, with production per hectare of 1500 to 2000 kg/ha. Under this context in to highlight the great importance of good crop management soybean crop, and have a competitive agriculture covering the shortfall of demand far the crop in the transformations of fats and oils. Key words: Agronomic management, soybean, soil and climate, production, performance, productivity, profitability, proteins, legume, agrological collect, analyzer, importance, fertilization, weed, ground preparation, planting, inoculation, irrigation, pests, diseases, harvesting.